Senior Tourists’ Well-being, Happiness, and Satisfaction with Life: A Systematic Literature Review - Câmara, Ester; Pocinho, Margarida; Neves de Jesus, Saúl; Agapito, Dora (Journal of Tourism, Sustainability and Well-being, 2024)
The perception of well-being through tourism improves the quality of life of tourists, and for senior tourists, this relationship is even more promising. While the association between tourism and mental health is clear, the processes involved are not always clarified. Thus, this systematic literature review aims to explore and systematise the benefits of senior tourism for well-being, happiness, and satisfaction with life. Following the PRISMA method, the search was undertaken on platforms SCOPUS and Web of Science, using the research terms “senior tourism”, “elderly tourism”, “well-being”, and “life satisfaction”. Articles were included, if published after 2018, peer-reviewed, in English, concerning an overview of senior well-being and tourism. After applying the inclusion and exclusion criteria, the final sample comprised 16 articles. Senior tourists experience higher well-being, happiness, and satisfaction with life when their goals are of high valence, more likely to be achieved, coherent with the activities, and when they feel pleasure associated with achieving those goals. Still, senior tourists’ happiness, life satisfaction and well-being are associated with four central elements: interpersonal relationships; time and resource management; achievement of goals and objectives; and management of the personal meaning attributed to the experience. Theoretical and empirical implications are further discussed.